2021
DOI: 10.3389/fnut.2021.790582
|View full text |Cite
|
Sign up to set email alerts
|

Solanum Fruits: Phytochemicals, Bioaccessibility and Bioavailability, and Their Relationship With Their Health-Promoting Effects

Abstract: The Solanum genus is the largest in the Solanaceae family containing around 2,000 species. There is a great number of edibles obtained from this genus, and globally, the most common are tomato (S. lycopersicum), potato (S. tuberosum), and eggplant (S. melongena). Other fruits are common in specific regions and countries, for instance, S. nigrum, S. torvum, S. betaceum, and S. stramonifolium. Various reports have shown that flavonoids, phenolic acids, alkaloids, saponins, and other molecules can be found in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 111 publications
0
22
0
1
Order By: Relevance
“…Since this plant is a short season crop, it can be preserved for long periods of time, and requires minimum inputs ( 46 ). Since it is grown in a wide range of climates, the potato tuber represents an excellent plant candidate to be used as a reservoir for producing natural metabolites ( 47 ). However, while this organ has been shown to accumulate high and diversified members of phenylpropanoids in the cultivated and wild potato species ( 48 , 49 ), it is devoid of carotenoids ( 50 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since this plant is a short season crop, it can be preserved for long periods of time, and requires minimum inputs ( 46 ). Since it is grown in a wide range of climates, the potato tuber represents an excellent plant candidate to be used as a reservoir for producing natural metabolites ( 47 ). However, while this organ has been shown to accumulate high and diversified members of phenylpropanoids in the cultivated and wild potato species ( 48 , 49 ), it is devoid of carotenoids ( 50 ).…”
Section: Introductionmentioning
confidence: 99%
“…Various species in this genus have completed various pharmacological research to verify and validate their ethnopharmacological usage. However, various reviews of the Solanum genus have been published, most of which focused on a single species [14,[27][28][29][30]. Table 3 summarizes the scientific literature and reveals a variety of ethnopharmacologically based traditional insect repellents derived from Solanum plants utilized by local ethnic communities in various countries to avoid mosquito bites.…”
Section: Ethnopharmacological Usementioning
confidence: 99%
“…These compounds have been linked to various health-promoting activities in the fight against several noncommunicable diseases, which are the leading causes of death worldwide. Many species belonging to this genus present a huge range of pharmacological activities such as anticancer, hepatoprotective, antimalarial, anthelmintic, and other activities [ 14 ]. Plants in this family are recognized for having a wide spectrum of alkaloid compounds, some of which are therapeutically the most potent.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, the toxicity studies of the isolated compounds and extracts of S. lyratum may have been overlooked by researchers, while few studies have found the toxic potential of Solanum glycoalkaloid [125]. The toxic properties of Glycoalkaloids including solamargine (8) have been reviewed by Sinani AI S.S.S. et al are due to (1) their ability to disrupt cell-membrane function by complexation with membrane 3β-hydroxysterols to form aggregates and damage the membrane integrity [126],…”
Section: Toxicologymentioning
confidence: 99%
“…In the last ten years, dozens of reviews on the research progress of Solanum plants have been published, occasionally referring few phytochemistry and pharmacological reports on S. lyratum [5][6][7][8] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%